A neuroscience agenda for counseling psychology research - Gonçalves, Óscar F. (2014)
Recent advances in the field of neuroscience have dramatically changed our understanding of brain– behavior relationships. In this article, we illustrate how neuroscience can provide a conceptual and methodological framework to understand our clients within a transdiagnostic developmental perspective. We provide directions for integrating neuroscience into future process and outcome research. We present examples on how neuroscience can be integrated into researching the effects of contextual counseling interventions. We posit that interpersonal and environmental factors, such as neurotoxic factors (e.g., emotional neglect, stress), positive neurodevelopmental factors (e.g., nurturing and caring, environmental enrichment), and therapeutic interventions influence psychological processes (executive control, behavioral flexibility, reinforcement learning and approach motivation, emotional expression and regulation, self-representation and theory of mind). These psychological processes influence brain networks (attention, motivational, emotional regulation, social cognition), which influence cognitive, social, emotional, identity, and vocational development.